Research on High Buck DC-DC Converters Based on Resonant Switched Capacitor and LLC Circuits - Zhuxuan Tian; Yuan Wang; Haijun Han; Qi Zhang; Chen Zhang; Yuqing Bu; Yueshi Guan (IEEE Access, 2025)
As the power consumption of data center continues to increase, the topology of their power supply has become a significant area of concern. This paper investigates the performance of diverse circuit topologies in pre-step-down scenarios (48V to 8V-6V) based on the 48V bus mechanism proposed by Google. This paper employs the resonant switched capacitor (RSC) converter and LLC resonant converter as case studies, elucidating their operational principles and optimizing them for the pre-buckling scenario. Subsequently, test prototypes of the RSC converter and LLC converter, with a power level of 200W, were constructed, resulting in a peak efficiency of 95.5% and a power density of 544.15W/in3 for the RSC converter; and a peak efficiency of 96.6% and a power density of 93.8W/in3 for the LLC converter. Ultimately, this paper compares RSC, LLC and MASC in terms of working efficiency, power density and manufacturing cost, based on experimental data and the high-quality topologies proposed by relevant scholars in recent years. The aim is to provide a reference for selecting the pre-step-down topology for data center power supply.